Adrenocorticotropic hormone in patients with West syndrome and progression to Lennox-Gastaut syndrome - Campos-Olazabal, Patricia (2021)
Background: This paper will evaluate the use of adrenocorticotropic hormone as a therapy modality for West syndrome and the time required for development of the severely progressive form of West syndrome (LGS, Lennox-Gastaut syndrome). There is little data on this condition for our population. Material and Methods: This is a cohort review in which 139 patient records were evaluated in two pediatric units in Lima, Peru; and they were analyzed between 2000 and 2010. All patients who met the following criteria were included in the study: massive spasms, delayed psychomotor development, and hypsarrhythmia in electroencephalogram (EEG) tracing. Adrenocorticotropic hormone was administered to a group of patients as post-diagnosis therapy. The follow-up period for these patients was 10 years. Results: The hazard ratio (HR) for progression to Lennox-Gastaut Syndrome in patients using adrenocorticotropic hormone was 0.45 (95% CI: 0.24-0.83, p= 0.011) compared to those without adrenocorticotropic hormone. Adjusted RR for progression to Lennox-Gastaut Syndrome for all variables studied (age of onset, sex, frequency of seizures, etiology, and time from diagnosis to therapy initiation) in patients who used adrenocorticotropic hormone was 0.56 (95% CI 0.29 to 0.08, P= 0.085) compared with those without adrenocorticotropic hormone. Conclusions: The use of adrenocorticotropic hormone in patients with West syndrome could protect against progression to Lennox-Gastaut syndrome. We consider this supports the evidence found in populations similar to ours, and we believe this finding could be confirmed with clinical trials.